UMBILICAL CORD CORTISOL LEVELS IN TERM AND LATE-PRETERM NEWBORNS - Martinovska, Iskra; Laban Gucheva, Nevenka; Naunova Timovska, Silvana; Kocevska, Ana; Baevska Vuchkovikj, Tatjana; Jovanoski, Afrodita Stomnaroska (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Cortisol, a glucocorticoid hormone secreted by the adrenal cortex, plays a pivotal role in human physiology, particularly in stress response regulation, immune function, and metabolic homeostasis. In the perinatal period, cortisol becomes a critical determinant of neonatal outcomes, as it drives the maturation of key fetal organs and facilitates the transition from intrauterine to extra uterine life. A surge in fetal cortisol levels during late gestation is integral to the development of the lungs, liver, and brain, which are essential for postnatal survival. Moreover, the umbilical cord, as the primary channel of maternal-fetal exchange, provides an invaluable window into the hormonal state of the fetus at birth. An observational prospective study analyzing umbilical cord blood cortisol levels, focusing on their associations with gestational age, was conducted at the Mother Teresa Hospital in Skopje, and 88 samples were obtained for analysis. The aim was to compare cortisol levels in healthy and appropriate for gestational age (AGA) newborns, depending on their gestational age. The results showed a mean cortisol level of 93.41 [95%CI 82.72 – 104.10]. In term infants the mean cortisol level was significantly higher, with a mean value of 100.60 [95%CI 88.940 – 112.259], than in preterm ones where mean cortisol level was 51.91 [95%CI 40.528 – 63.301], with a statistically significant difference (p<0.0012). The significant associations between cortisol levels and gestational age highlight the potential utility of umbilical cord blood cortisol as a biomarker for assessing neonatal stress and adaptation. Keywords:   cortisol , newborn , umbilical cord , delivery,  gestational age ,  term,  preterm.